Effects of different strategies on high thrombus burden in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary catheterization. Issue 8 (December 2019) - Xiao, Yuyang; Fu, Xianghua; Wang, Yanbo; Fan, Yanming; Wu, Yanqiang; Wang, Wenlu; Zhang, Qian
Abstract : Objective: This study aimed at evaluating efficacy and safety of thrombus aspiration and intracoronary-targeted thrombolysis on coronary thrombus burden in ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous catheterization, comparing their effects on myocardial perfusion through index of microcirculatory resistance (IMR) and single-photon emission computed tomography (SPECT). Participants and methods: From January 2017 to January 2018, STEMI patients with high thrombus burden undergoing primary catheterization were enrolled and randomly assigned to receiving thrombus aspiration (TA group) or intracoronary thrombolysis (IT group). IMR, SPECT, and other conventional measurements were adopted to assess myocardial perfusion. Major adverse cardiovascular events (MACEs) and complications were recorded over a 90-day follow-up and a 12-month follow-up after the procedure. Results: The study consisted of 38 patients in the IT group and 33 in the TA group. After recanalization, thrombus burden score, corrected thrombolysis in myocardial infarction (TIMI) frame count, the proportion of TIMI myocardial perfusion 3 grade, and IMR in the IT group were significantly better than those of the TA group ( P <0.05). During the 90-day follow-up, no difference was observed in cardiac function and MACEs. During the 12-month follow-up, there were significant differences in infarct size of SPECT (18.56±8.56 vs. 22.67±7.66, P =0.046), left ventricular ejection fraction of echocardiography (58.13±5.92 vs. 55.17±5.68, P =0.043), and the composite MACEs between the two groups ( P =0.034). Conclusion: Thrombus aspiration and intracoronary-targeted thrombolysis are effective and safe strategies in managing high coronary thrombus burden in STEMI patients. Compared with aspiration, intracoronary-targeted thrombolysis is more beneficial in improving myocardial microcirculation perfusion.